Christelle Fischer-Bovet and Sitta von Reden (eds) Comparing the Ptolemaic and Seleucid Empires: Integration, Communication, and Resistance. - Stavrou , Dorothea (Journal of Greek Archaeology, 2024)
This volume is a welcome addition to the comparative study of Seleucid and Ptolemaic kingdoms. In the introduction, the editors present the aims of the book, its structure and the approaches taken by the 10 contributions, most of which are co-authored. The volume is divided into three sections, which deal with the internal organization of the kingdoms, the forms of communication and exchange and the manifold relationship between the local elites and the kings.